Emerging World and Artificial Intelligence; Any Ethical Consideration? (Global Journal of Human-Social Science, 2019)
The paper attempts a moral consideration on artificial intelligent. It acknowledged that the progression of artificial intelligence has constituted a lot of things in the 21st century; teaching, war, politics, automobile, telecommunication, economics, social and political system, in fact almost every sphere of mankind. However, this progression as pose some questions on the ethical issues leave many educators wondering how to address moral, ethical, and philosophical issues concerning this use of AI. Among these questions is whether the same ethical standard accrued to man should also be accrued or given to AI (Robot), does AI has any intrinsic value that demands any moral consideration? Beyond these, the study investigates different approaches to AI ethics and how to weigh them. One approach is to the question of "How will we have a tendency to initiate or propose AI systems which will perform ethically?" Another is, "How can we have an inclination to act ethically as programmers and system designers, to decrease the risks that make our systems and codes act unethically?" It is worth noting that philosophers continue to debate the question of whether it makes sense to say that a cybernetic system can be said to be ethical or unethical.
Keywords: emerging world; artificial intelligence; human intelligence; ethics; morality